2008
DOI: 10.1103/physrevc.77.024909
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic radiation from nuclear collisions at ultrarelativistic energies

Abstract: The hot and dense strongly interacting matter created in collisions of heavy nuclei at RHIC energies is modeled with relativistic hydrodynamics, and the spectra of real and virtual photons produced at midrapidity in these events are calculated. Several different sources are considered, and their relative importance is compared. Specifically, we include jet fragmentation, jet-plasma interactions, the emission of radiation from the thermal medium and from primordial hard collisions. Our calculations consistently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(161 citation statements)
references
References 32 publications
9
152
0
Order By: Relevance
“…[27] that annihilation and Compton processes can also lead to the conversion of a quark or gluon jet into a photon. Perturbative estimates of this process at leading order indicate a sizable contribution to the total direct photon yield at intermediate p T between 3 and 6 GeV/c at RHIC energies [28][29][30][31]. The same was found for the production of virtual photons and lepton pairs [31,32].…”
Section: Flavor Conversions In Quark Gluon Plasmasupporting
confidence: 53%
See 2 more Smart Citations
“…[27] that annihilation and Compton processes can also lead to the conversion of a quark or gluon jet into a photon. Perturbative estimates of this process at leading order indicate a sizable contribution to the total direct photon yield at intermediate p T between 3 and 6 GeV/c at RHIC energies [28][29][30][31]. The same was found for the production of virtual photons and lepton pairs [31,32].…”
Section: Flavor Conversions In Quark Gluon Plasmasupporting
confidence: 53%
“…[35] it was estimated that the sum of all direct photon sources leads to small and negative direct photon v 2 between 3 and 5% at intermediate p T . However, later it was noted that the result depends crucially on details of the fireball simulation and might be much closer to zero [31]. First experimental results are compatible with zero with sizable uncertainties [36,37].…”
Section: -2mentioning
confidence: 49%
See 1 more Smart Citation
“…It has been shown that the contributions from different sources of direct photons (apart from thermal) become significant in the photon p T spectrum for p T > 3 GeV/c [14]. However, the thermal radiation dominates the elliptic flow of direct photons up to a much larger p T (∼ 5 GeV/c) as the v 2 contributions from other sources are marginal in that range [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent phenomenological refinements [16,17] suggest that the QGP enhancement of direct γ production may be smaller than previously expected and partly cancelled by the quenching of fragmentation photons. Still, there is no calculation to date that consistently includes known nuclear matter effects, such as the Cronin effect [18,19,20], shadowing [21,22], and cold nuclear matter energy loss [23], to provide quantitative guidance for the relative strength of initial-and final-state modifications in the observed γ cross sections.…”
Section: Introductionmentioning
confidence: 99%